KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND AWARENESS: TPQ Darul Furqon Cirebon Case Study (JIKE : Jurnal Ilmu Komunikasi Efek, 2022)
Growing consumer awareness can have an impact on a company's success. Brand awareness is one of the efforts to build a corporate image in this digital era. As a non-profit business actor, the Darul Furqon Educational Institute (TPQ) in Cirebon Regency does this. As a result, effective marketing communication is required to raise brand awareness in TPQ Darul Furqon. The purpose of this research is to identify the marketing communications undertaken by TPQ Darul Furqon, as well as the various challenges encountered in raising brand awareness. A qualitative approach was used with a purposive sampling informant technique to conduct research on three different categories of Parental Society. Data analysis entails gathering and categorizing information gleaned from observations, interviews, and documentation. According to the study's findings, TPQ Darul Furqon as a brand employs six marketing elements: advertising, sales promotion, direct marketing, internet marketing, procurement of religious events and experiences, and word of mouth. Word-of-mouth marketing communication is thought to be more effective in the surrounding community. The main barriers to marketing communications in building brand awareness are a lack of human resources, facilities, and infrastructure.Keywords : Marketing Communication, Marketing Mix, Brand Awareness